Spatial distribution and survival of human and goat mesenchymal stromal cells on hydroxyapatite and β‐tricalcium phosphate. (18th December 2012) - Prins, Henk‐Jan; Fernandes, Hugo; Rozemuller, Henk; van Blitterswijk, Clemens; de Boer, Jan; Martens, Anton C. M.
Abstract: The combination of scaffolds and mesenchymal stromal cells (MSCs) is a promising approach in bone tissue engineering (BTE). Knowledge on the survival, outgrowth and bone‐forming capacity of MSCs in vivo is limited. Bioluminescence imaging (BLI), histomorphometry and immunohistochemistry were combined to study the fate of gene‐marked goat and human MSCs (gMSCs, hMSCs) on scaffolds with different osteoinductive properties. Luciferase–GFP‐labelled MSCs were seeded on hydroxyapatite (HA) or β ‐tricalcium phosphate (TCP), cultured for 7 days in vitro in osteogenic medium, implanted subcutaneously in immunodeficient mice and monitored with BLI for 6 weeks. The constructs were retrieved and processed for histomorphometry and detection of luciferase‐positive cells (LPCs). For gMSCs, BLI revealed doubling of signal after 1 week, declining to 60% of input after 3 weeks and remaining constant until week 6. hMSCs showed a constant decrease of BLI signal to 25% of input, indicating no further expansion. Bone formation of gMSCs was two‐fold higher on TCP than HA. hMSCs and gMSCs control samples produced equal amounts of bone on TCP. Upon transduction, there was a four‐fold reduction in bone formation compared with untransduced hMSCs, and no bone was formed on HA. LPCs were detected at day 14, but were much less frequent at day 42. Striking differences were observed in spatial distribution. MSCs in TCP were found to be aligned and interconnected on the surface but were scattered in an unstructured fashion in HA. In conclusion, the spatial distribution of MSCs on the scaffold is critical for cell–scaffold‐based BTE. Copyright © 2012 John Wiley & Sons, Ltd.